The Construction of a New Hearth (Ocak) and Community in Kizilbash/Alevi Society: Anşa Bacı and Keçeli Sıraçs (Journal of Alevism-Bektashism Studies, 2018)
During the reign of Sultan Abdülhamid II, the communities of Kizilbash, also known as Alevis were particularly monitored closely by the provincial and central bureaucracy due to the specific circumstances of the period. Drawing on the resulting documentation, this paper investigates the littlestudied rise and development of the community headed by Anşa Bacı. Anşa Bacı and her family were members of the tribe (aşiret) of Beydili- Sıraç (also known as the tribe of Keçeli Sıraç) which was affiliated with the holy hearth (ocak) of Hubyar. Serving as a sofu (ascetic) within the Hubyar Ocak, Anşa Bacı’s husband Veli had sharply criticized the current dede (religious leader), causing a historic rift among the Hubyar. After her husband’s death, Anşa assumed his position of leadership among their followers within the tribe of Keçeli Sıraç. Some of the regulations allegedly realized by Anşa Bacı within the community soon raised the state’s attention. As a consequence of a denunciation accusing Anşa Bacı and her family of presenting Anşa’s son as “Mahdi” to their followers based in and around Sivas, Tokat, Niksar, Amasya, Zile and Yozgat, collecting charity from the Keçeli Sıraç claiming community in property and helping to arm the community, state officials initiated a formal investigation. Although state officials were unable to find any solid evidence to support these allegations, Anşa Bacı, her sons and her son-in-law, as well as other family members were exiled to Damascus. When Anşa Bacı returned to Zile, she became a charismatic figure and composed a new religious community and hearth, the Anşa Bacılılar, which still exists today. These historic developments, therefore, resulted in a permanent separation between the followers of Anşa Bacı and Hubyar, directly influencing the two communities’ religious positions and consolidating them in their current status.